Factors associated with exclusive breastfeeding of children under six months of age in Cote d'Ivoire - Ibrahima Koffi; Esme Marie Laure Essis; Iba Bamba; Kaudjhis Rh Assi; Loukou Léandre Konan; Joseph Aka (BMC, 2023)
Abstract Background Despite benefits of exclusive breastfeeding (EBF) and its strategic place in the national guidelines for infant and young child feeding, its practice remains insufficient in Cote d'Ivoire. It is therefore important to identify its early stopping associated factors. We aimed to (i) assess the extent of children's exposure to exclusive breastfeeding and the associated explanatory factors for discontinuation before six months, and (ii) to profile non-exclusively breastfed children and interrelationships between these factors. Methods A secondary analysis of data from the 2016 Cote d'Ivoire Fifth Multi Indicator Cluster Survey (MICS5) of 980 children under six months of age was conducted in this study. Data were analyzed using the actuarial method of survival hazard estimation combined with the Wilcoxon (Gehan) test, discrete time proportional hazards regression models, and Multiple Correspondence Analysis (MCA) to profile the children. Results Maternal exposure to counseling session, age at delivery, and child sex were significantly associated with the likelihood of discontinuing exclusive breastfeeding before the first six months of life. Children deprived of EBF resided in urban areas, in high and very high economic welfare households. Their mothers had a secondary education or higher and had three or fewer children. Logistic analysis showed that health status and sex of the child were significantly associated (P < 0.001) with exclusive breastfeeding. An extremely important and rarely studied factor is that children who were sick in weeks prior to the survey were more likely to remain exclusive breastfeeding (adjusted OR 1.80; 95% Confidence Interval (CI) 1.452, 2.234). Girls are less likely to be exclusively breastfed than boys (adjusted OR 1.48; 95% CI 1.22, 1.798). Low standard of living was associated with early cessation of EBF (adjusted OR 2.15; CI 1.325, 3.499). The duration of the exclusive breastfeeding was significantly longer among mothers with high exposure to medical discourse (adjusted OR 0.74; CI 0.595, 0.91). Conclusions Improving the practice of exclusive breastfeeding in Cote d'Ivoire requires strengthening the capacities of health professionals in terms of advice and assistance to mothers for the practice of exclusive breastfeeding and its maintenance until six months of age, regardless of the health status and sex of the child.